Uso de mecânica da gamificação para a busca de indícios de aprendiazem significativa no ensino de gráficos estatísticos - Santos, Andrieli dos (2022)
This text refers to the dissertation of the master’s course of the Postgraduate Programme in Science and Mathematics Teaching at the University of Passo Fundo. This project investigated possible signs of significant learning, from the use of mechanics present in digital and analog games. These mechanics were used as a strategy to enhance the study of statistical graphs: histogram, boxplot, and scatter diagram. A study was carried out in a class of the 7th year of Elementary School II of a public school in the city of Marau/RS, Brazil. From the premise that the student needs to be willing to learn, we sought to develop the study of statistical graphics within a proposal that resembles the environments proposed by games and, thus, arouse predisposition and motivation for pedagogical activities and problem solving. The analyzes were based on the Theory of Meaningful Learning by David Paul Ausubel, as well as the use of gamification mechanics. The guiding documents of education in the municipality, the Brazilian National Common Curricular Base, and the National Curriculum Parameters, which prescribe the teaching of Statistics, were also taken to support the statistical contents addressed in this study. Thus, the use of gamification was investigated as a strategy to contribute to the teaching of the chosen statistical graphics and as a way to enhance student engagement in this process, and thus make learning meaningful. To this end, the gamification mechanics such as teamwork, scoring, narrative, rules, levels, and awards were considered. The research carried out considers a qualitative and participant approach, involving data collection from the teacher/researcher's records in the logbook and from the answers obtained in the questionnaire applied after the end of the research. Based on these instruments it was concluded that the performance of activities in a collaborative way and in a competitive context contributed to the socialization and interaction among students; moreover, the development of activities in teams contributed for the students to help each other in their difficulties. The classes became dynamic, having the students as active participants in the construction of learning about graphs. The results indicate that the development of the didactic sequence made it possible to verify the presence of well-structured prior knowledge regarding the reading and interpretation of graphs; moreover, it was possible to take such knowledge as a starting point for the expansion of knowledge necessary for the construction of the graphs studied. Regarding the format of the material, proposed in slides, it contributed to make the classes more dynamic, providing more time for dialogues, content explanation, and application of the concepts studied in practical activities. The educational product that accompanies this dissertation refers to a didactic sequence aimed at mathematics teachers of the final grades of elementary school and includes activities focused on the study of statistical graphics. This educational product is available on the http://educapes.capes.gov.br/handle/capes/717084>.